Anti-enterovirus 71 effects of chrysin and its phosphate ester. - Jianmin Wang; Ting Zhang; Jiang Du; Sheng Cui; Fan Yang; Qi Jin (PLoS ONE, 2014)
Enterovirus 71 (EV71) can cause severe disease and even lead to death in children, and an effective antiviral drug is currently unavailable. The anti-EV71 effect of chrysin (5,7-dihydroxyflavone), a natural flavonoid commonly found in many plants, was tested in this report. By using the predicting program Autodock 4.0 and an in vitro protease inhibition assay, we found that chrysin could suppress viral 3Cpro activity. Replication of viral RNA and production of viral capsid protein and the infectious virion were strongly inhibited by chrysin, without noticeable cytotoxicity. Cytopathic effects on cells were also prevented. Diisopropyl chrysin-7-yl phosphate (CPI), the phosphate ester for chrysin, was generated through a simplified Atheron-Todd reaction to achieve stronger anti-viral activity. CPI was also able to bind with and inhibit viral 3Cpro activity in vitro. As expected, CPI demonstrated more potent antiviral activity against EV71.